Synthesis and Thermal Characterization of Polybutadiene Azide - LAMOURI, S.; IHDENE, Z. (Asian Journal of Chemistry, 2010)
The present work presents the possibility of introducing new functional groups on the chains of polybutadiene. The polybutadiene is obtained by a radical polymerization in a solution. In an intermediate step, an addition of bromine (Br2) is carried out. The azide group (-N3) is grafted on the polybutadiene chain by a reaction of substitution with bromine under well defined conditions. The virgin and modified polymers are characterized by infrared spectroscopy, differential scanning calorimetry analysis, thermogravimetric analysis and elemental analysis. These studies confirm the existence of the grafted group and evaluation of quantify their percentages.